Calamities, common interests, shared identity: What shapes altruism and reciprocity? - Cevat Giray Aksoy; Antonio Cabrales; Mathias Dolls; Ruben Durante; Lisa Windsteiger (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
We conduct a large-scale survey experiment in nine European countries to study how priming a major crisis (COVID-19), common economic interests, and a shared identity influences altruism, reciprocity and trust of EU citizens. We find that priming the COVID-19 pandemic increases altruism and reciprocity towards compatriots, citizens of other EU countries, and non-EU citizens. Priming common European values also boosts altruism and reciprocity but only towards compatriots and fellow Europeans.Priming common economic interests has no tangible impact on behaviour. Trust in others is not affected by any treatment. Our results are consistent with the parochial altruism hypothesis, which asserts that because altruism arises out of inter-group conflict, humans show a tendency to favor members of their own groups.
Keywords: D72; H51; H53; H55; O52; P52; 330; COVID-19; Europe; altruism; reciprocity; survey experiment